An anti-collision system for tower cranes considering lifting heavy objects. Issue 1 (1st November 2022) - He, Dongfeng; He, Junping; Li, Zhibin; Huang, Bo; Cheng, Hongliang
Abstract: Most of the traditional tower crane anti-collision solutions only consider the ideal working environment of the tower crane without lifting heavy objects or fail to consider the collision under the condition of lifting heavy objects, which has certain limitations in practical engineering applications. This paper proposes an anti-collision system for tower cranes that considers lifting heavy objects. The system introduces the concept of the dangerous area of cylindrical heavy objects, and explains in detail the anti-collision principle of tower cranes when lifting heavy objects. At the same time, the specific scheme of hardware controller and software design of the system is introduced. The system makes the tower crane anti-collision system closer to the real working situation, and is a supplement to the research and application field of tower crane anti-collision.